Investigation of the nanocrytalline SnO2 Synthesized by Homogeneous Precipitation - Abdel-Salam, Mahmoud. N.; Abdel-Rahim, M. A.; Gaber, A.; Abdel-Latief, A. Y. (JOURNAL OF ADVANCES IN CHEMISTRY, 2015)
Nanocrystalline tin dioxide synthesized by the homogeneous pre cipitation method using the reaction of tin tetrachloride pentahydrate and urea solutions has been investigated. The nanocrystalline powder has been traced at different calcination temperatures (300ºC-1050ºC), and then characterized by using Thermogravemetric analysis, differential thermal analysis and x-ray diffraction. The microstructure of the obtained nanoparticles has been examined by scanning and transmission electron microscopy. The average crystallite size, determined by x-ray diffraction, was found to be in the range of 3 –30 nm. The analysis exhibited a tetragonal phase. Optical properties were investigated by a UV–vis absorption spectrophotometer. The calculated optical band gap lies between 4.47–3.71 eV as a result of increasing the calcination temperatures and crystallite size. Surface area and porosity of SnO2 nanoparticles are measured. Specific surface area which is related to pore volume and decreases from 155 m2/g at 100ºC to 3.3 m2/g at 1050ºC.